The Voyage Out. - Woolf, Virginia, 1882-1941 (Floating Press, 1915)
The first novel in what would be a remarkable but tragically curtailed creative career, Virginia Woolf's The Voyage Out recounts the tale of Rachel Vinrace's literal and metaphorical journey. En route to South America on one of her father's ships, Rachel undertakes her own voyage of self-discovery as she interacts with a motley crew of passengers, through whom Woolf takes the opportunity to savagely satirize the bourgeois mores of Edwardian England.